Implementation of Zoning-Based New Student Admission System Policy at the High School Level in Bandung City, West Java, Indonesia - Egy Herdiansyah Setiawan; Salwaa Sahdania; Heru Nurasa; Mas Halimah (Jurnal Manajemen Pelayanan Publik, 2022)
The purpose of this study was to determine the implementation of the Zoning System policy in the Admission of New Students in Bandung City at the senior high school (SMA) level and to see how the implementation of the policy was implemented at the high school level in Bandung, West Java. The research method used is descriptive research method with a qualitative approach. In the research conducted, primary data and secondary data obtained through literature study techniques, field studies (interviews and observations) were used, besides that purposive techniques were also used to determine informants in the study. The results of this study were analyzed using the Miles and Huberman model. The results of the study indicate that the government has not been optimal in its implementation, this is viewed from several aspects, namely, organizations where the government has used its resources, interpretations or ways of delivering government that are not easy to understand, and its implementation is in accordance with the direction of goals, and objectives, aspects of the principle Therefore, there is a need for policy consistency and policy evaluation in regulations related to this zoning system in order to realize the objectives of this policy.